Gaps and Actions in Health Improvement from Hong Kong and Beyond All for Health - Fong, Ben Yuk Fai.; Wong, William Chi Wai. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book provides a timely review on what has been accomplished, and what remains amiss, following the World Health Organization's 1978 'Health for All' campaign, by identifying enduring gaps in health care within a global context. The WHO declaration of "Health for All by the Year 2000" mapped out a road towards primary health care for all people and demarcated it as essential for human progress in terms of economic development and social justice. However, 45 years have gone by, and most societies and countries have yet achieved 'health for all', despite so much having changed in technology, disease patterns, and population demographics. In promoting community health and improving service delivery, the book advocates the development and implementation of "All For Health" strategies to steer stakeholders in the right direction towards universal health care. The book covers the gaps and actions in health improvements, the 'All For Health' strategies, and the Health in All Policies (HiAP), reviewing and discussing issues through both Asian and international examples. Contributors include both academics and practitioners from diverse professional backgrounds including medicine, nursing, pharmacy, allied health, dietetics, social sciences, life sciences, education, business, administration, law, and public policy. Essential to scholars in public health and related disciplines, this book is also useful to policymakers, community and public health practitioners, and health care executives and interns.
Achievements In HFA2000 Since 1978 -- Difficulties And Barriers In Accomplishment Of HFA 2000 -- Global Implementation Of Primary Health Care -- Filling The Gaps In Youth Health And Wellness -- Video Conferencing-Delivered Health Intervention -- Lifestyle Risk Factors Patterns And Development Trends In Hong Kong -- Sustainable Green Environment And Health Improvement -- Equity In Healthcare For Ethnic Minorities -- Promotion Of Breastfeeding As An All For Health Strategy -- Digital Health And Technology Adoption -- Active Ageing And Healthy Ageing -- Promotion Of Healthy Lifestyle For Healthy And Safe Cities - The Case Of Hong Kong, China -- District Health Care Movement -- Medicalisation In Healthcare -- Effect Of Offering Organisational Supports To Employees With Responsibilities For Elderly Family Members: Evidence From China -- Experiences In Working At Residential Care Home For The Elderly: Voices From Health Care Workers -- Residential Choices Of The Elderly Under Medical And Aged Care Integration: Evidence From Shanghai.
Keywords: Demography; Population; Medical care; Public health; Social policy; Medical education; Population and Demography; Health Care; Public Health; Social Policy; Medical Education